2021
DOI: 10.1080/10641963.2021.1925681
|View full text |Cite
|
Sign up to set email alerts
|

Association between the combined fat mass and fat-free mass index and hypertension: The Tohoku Medical Megabank Community-based Cohort Study

Abstract: Background: A higher body fat percentage is associated with hypertension, even in non-obese individuals. The difference in body composition may be related to hypertension. The fat mass index (FMI) and fat-free mass index (FFMI) are proposed indicators of body composition. This study aimed to examine the relationship of a combination of FMI and FFMI with hypertension. Methods: We conducted a cross-sectional study of 5,058 men and 11,842 women aged ≥ 20 years in the Miyagi Prefecture, northeastern Japan. The FMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Contrary to our results, some investigations in adult and pediatric populations established that FFM is positively related to systolic, diastolic, or mean blood pressure (49)(50)(51)(52)(53)(54)(55). Korhonen et al (50) attribute this nding to muscle mass properties; during daytime and contraction, skeletal muscles release myokines that may increase blood pressure.…”
Section: Total Fatp and Ffmcontrasting
confidence: 99%
“…Contrary to our results, some investigations in adult and pediatric populations established that FFM is positively related to systolic, diastolic, or mean blood pressure (49)(50)(51)(52)(53)(54)(55). Korhonen et al (50) attribute this nding to muscle mass properties; during daytime and contraction, skeletal muscles release myokines that may increase blood pressure.…”
Section: Total Fatp and Ffmcontrasting
confidence: 99%
“…Han et al [ 55 ] also suggested that body fat and skeletal muscle are strongly associated with diabetes and may be more useful indicators than BMI. Takase reported that the fat mass index calculated as the fat mass divided by the height squared was strongly associated with hypertension in a cross-sectional study of 5,058 men and 11,842 women aged ≥ 20 years in the Miyagi Prefecture, northeastern Japan [ 57 ]. With respect to BMD, Dennison et al [ 71 ] argued that the total femur and femoral neck BMD exhibited a positive association with insulin resistance, with a stronger association in women.…”
Section: Discussionmentioning
confidence: 99%
“…However, these obesityrelated indicators cannot distinguish between body fat mass and muscle mass. Some studies have shown that the total body fat percentage or trunk fat and left and right leg fat are more strongly correlated with diabetes [49][50][51][52] or hypertension [49,[53][54][55][56][57] than obesity-related indicators. These previous studies showed that having a large amount of fat in the body is not unhealthy but rather that fat has different effects on health depending on which part of the body it is located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it may be more reliable to use BFP as an indicator of obesity (21). Takase has demonstrated that it is BFP rather than BMI that affects blood pressure (22). A Korean cohort study similarly showed that increased body fat was a predictor of hypertension (23).…”
Section: Figurementioning
confidence: 99%